اسلامی قوانینِ دفاع کی معنویت عہدِ حاضر میں -------------------------------------------------------------------------------------------------- The Meaningfulness of Islamic Principles of Defence in Modern Era - جدون, سعید الحق; شید, بخت (FIKR-O NAZAR فکر ونظر, 2016)
The defense is a legitimate right of every living being for sake of its survival both according to the common sense and the teachings of religions.  Islam has given this right to man, and considers it to be the chief guarantee for survival of humanity. Quran and sunnah have emphasized on the significance of self defense and state defense and the great scholars of Islam have elucidated this dimension of Islamic Law in their books. In the Prophetic era the system of defense and security was established on very dynamic and solid bases. Prophet PBUH has emphasized on the application of all security equipment and methods. Through the analogy the modern equipments of defense may be justified as long as they reconcile with the objectives of shariah and the betterment of mankind. In this article the author has tried to highlight the significance of rules and regulations pertaining to security and defense system in the light of Quran, sunnah and the sayings of jurists. Some points of view have also been analyzed in this regard.